Geoestatística no estudo da variabilidade espacial de atributos químicos e físicos do solo e da produtividade da pimenta-do-reino - Quartezani, Waylson Zancanella (2008)
The culture of Piper nigrum L. is one of the most profitable crops in the north of the Espírito Santo State. In view of the actual situation of nutritional management of culture adopted in the State, allied to the cultivation in regions of low natural fer